2015
DOI: 10.1021/acs.orglett.5b01052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cinnolin-3(2H)-one Derivatives from Rh-Catalyzed Reaction of Azobenzenes with Diazotized Meldrum’s Acid

Abstract: A synthetic method of a wide range of cinnolin-3(2H)-one derivatives is developed from the reaction of symmetrical as well as unsymmetrical azobenzenes with diazotized Meldrum's acid via Rh-catalyzed C-H alkylation followed by cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Moreover, Lee and Patel independently reported the facile synthesis of benzotriazoles from azobenzenes and organic azides through the Rh(III)‐ or Pd(II)‐catalyzed amination and cyclization reactions . Recently, Lee and our group described the construction of highly substituted cinnolinones derived from azobenzenes and α‐diazo esters under Rh(III) catalysis. Furthermore, other heterocycles such as cinnolines, 3‐acyl‐indazoles and indoles were also formed via the C−H functionalization followed by cyclization strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Lee and Patel independently reported the facile synthesis of benzotriazoles from azobenzenes and organic azides through the Rh(III)‐ or Pd(II)‐catalyzed amination and cyclization reactions . Recently, Lee and our group described the construction of highly substituted cinnolinones derived from azobenzenes and α‐diazo esters under Rh(III) catalysis. Furthermore, other heterocycles such as cinnolines, 3‐acyl‐indazoles and indoles were also formed via the C−H functionalization followed by cyclization strategy.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, the Lee and Kim groups independently reported the synthesis of cinnolin‐3(2 H )‐ones 153 by Rh(III)‐catalyzed direct C–H alkylation/annulation of azobenzenes 152 with diazotized Meldrum's acid (Scheme ) . Lee's group found that the symmetrical azobenzenes 152 cyclized at the less steric position with good yields. With those unsymmetrical azobenzenes, the reaction took place at the electron‐poor aryl ring.…”
Section: Synthesis Of Other Heterocyclesmentioning
confidence: 99%
“…Following the seminal work of Rovis et al, Cui and co‐workers developed a protocol for the synthesis of azepinone derivatives through the Rh III ‐catalysed C–H activation of benzamides with vinyl carbenoids . More recent reports of Rh III ‐catalysed C–H functionalisation using diazo compounds as coupling partners have come from the groups of Glorius, Wang, Chang, Xu and Yi, Liu, Zhou, Kim, Lee, Zeng, and Samanta . Although decent progress has been made in this area, we believe that such an interesting topic is worthy of further exploration.…”
Section: Introductionmentioning
confidence: 99%